New Therapeutic Approaches for Alzheimer’s Disease and Cerebral Amyloid Angiopathy - Saito, Satoshi; Ihara, Masafumi (Frontiers in Aging Neuroscience, 2014)
Accumulating evidence has shown a strong relationship between Alzheimer’s disease (AD), cerebral amyloid angiopathy (CAA), and cerebrovascular disease. Cognitive impairment in AD patients can result from cortical microinfarcts associated with CAA, as well as the synaptic and neuronal disturbances caused by cerebral accumulations of β-amyloid (Aβ) and tau proteins. The pathophysiology of AD may lead to a toxic chain of events consisting of Aβ overproduction, impaired Aβ clearance, and brain ischemia. Insufficient removal of Aβ leads to development of CAA and plays a crucial role in sporadic AD cases, implicating promotion of Aβ clearance as an important therapeutic strategy. Aβ is mainly eliminated by three mechanisms: 1) enzymatic/glial degradation, 2) transcytotic delivery, and 3) perivascular drainage (3-‘d’ mechanisms). Enzymatic degradation may be facilitated by activation of Aβ-degrading enzymes such as neprilysin, angiotensin-converting enzyme, and insulin-degrading enzyme. Transcytotic delivery can be promoted by inhibition of the receptor for advanced glycation end products (RAGE), which mediates transcytotic influx of circulating Aβ into brain. Successful use of the RAGE inhibitor TTP488 in Phase II testing has led to a Phase III clinical trial for AD patients. The perivascular drainage system seems to be driven by motive force generated by cerebral arterial pulsations, suggesting that vasoactive drugs can facilitate Aβ clearance. One of the drugs promoting this system is cilostazol, a selective inhibitor of type 3 phosphodiesterase. The clearance of fluorescent soluble Aβ tracers was significantly enhanced in cilostazol-treated CAA model mice. Given that the balance between Aβ synthesis and clearance determines brain Aβ accumulation, and that Aβ is cleared by several pathways stated above, multi-drugs combination therapy could provide a mainstream cure for sporadic AD.